Answer: -7
Explanation:
First, lets use the functions to find the answer to f(-8) and g(4)
f(-8) is the same as asking for the value of y when x is -8
Therefore, f(-8) = -5 (according to the graph)
Using the same rule, g(4) would be the value of y when x = 4 which,
according to the graph, g(4) = 3
Plug these values back into the original equation to get:
![-1*f(-8)-4*g(4)=?\\=-1*-5-4*3\\](https://img.qammunity.org/2023/formulas/mathematics/college/jbujl3rncqptfbgw15c185g3r7gz8bspfa.png)
using the order of operations, we will multiply the values first
![(-1*-5)+(-4*3)\\=5+(-12)\\=5-12\\=-7](https://img.qammunity.org/2023/formulas/mathematics/college/10jtllm0dnesonacrk0bth0yymijybgzg8.png)
Therefore, our final answer is -7